How to promote wellbeing in youth sport: Recommendations from the 2024 Copenhagen Consensus Conference - Nielsen, G.; Krustrup, P.; Rossing, N. N.; Elsborg, P. J.; Nøddesbo, J.; Krabbe, A.; Rashid, I.; Høj, B. B.; Mortensen, J.; Østergaard, S.; Skovgaard, T.; Ryom, K. A.; et al. (Scandinavian Journal of Medicine & Science in Sports, 2025)
On August 29 and 30, 2024, eight researchers and six expert practitioners within wellbeing and youth sport were gathered in Copenhagen to reach evidence-based consensus on how to promote wellbeing in and through youth sports. The consensus process integrated international research-based knowledge with practice-based knowledge into statements about key factors influencing wellbeing in youth sport. Based on this knowledge, practice and policy directed statements on how wellbeing in and through sport can be promoted were formulated. The consensus process and the resulting statements were based on a system approach to wellbeing in youth sport and how it can be promoted. Four system levels (the individual, interpersonal, community, and policy levels) were addressed in answering the following questions: (1) What characterizes wellbeing in sport for children and adolescents? (2) What characterizes sport environments that promote children and adolescents` wellbeing? (3) Which factors are important to consider in efforts to develop wellbeing promoting youth sport environments? (4) How can wellbeing in youth sport be promoted? In total, 19 consensus statement sentences were formulated on how young sports participants (3), parents/caretakers (5), coaches and leaders/managers (5), local sport communities (3) and sports federations (3) can promote wellbeing in youth sport.